Simple Kinect-based gesture tracker - Ryndel, Anders (My University, 2017)
This project has developed an alternative to standard touch-based control system by creating a gesture based system built on the Microsoft Kinect for Xbox 360. This system is required to be reliable, robust, and intuitive to use. The developed system uses a method that models a region around the user and classifies anything that extends from that region as a raised hand. It is a crude solution but proved very reliable when used by an experienced user. The intended purpose of this system is as a control device for a partner agent to be use with seniors. But the system turned out to have weaknesses that makes it less suitable than other possible solutions. Weaknesses includes that the system can be put into an error mode that needs knowledge of the system to recover from, something the intended semographic can’t be expected to have. This weakness could be improved upon with a better system, but it still leaves the more important weakness: that the ergonomical requirements of the primary target demographic, which can’t be expected to find constantly raising arms to the level of the head to be a comfortable work environment. It is likely that a parter agent user is better served by a hands-on controller, such as a controller for Playstation or XBox.
Keywords: Informations- och kommunikationsteknik; Robotteknik och automation; Information & Communication Technology; Robotics